2019
DOI: 10.3390/genes10020117
|View full text |Cite
|
Sign up to set email alerts
|

RNA 2′-O-Methylation (Nm) Modification in Human Diseases

Abstract: Nm (2’-O-methylation) is one of the most common modifications in the RNA world. It has the potential to influence the RNA molecules in multiple ways, such as structure, stability, and interactions, and to play a role in various cellular processes from epigenetic gene regulation, through translation to self versus non-self recognition. Yet, building scientific knowledge on the Nm matter has been hampered for a long time by the challenges in detecting and mapping this modification. Today, with the latest advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 217 publications
(257 reference statements)
2
156
0
Order By: Relevance
“…These mRNA cap modifications have been shown to have a wide variety of functions. For example, the m 7 G modification in the mRNA cap recruits the translation initiation machinery for cap-dependent translation, and Cap 1 2’O methylation can further enhance this translation (8, 10, 11). mRNA cap 2’O methylation has also been shown to prevent degradation of modified transcripts by exoribonucleases or serve as a motif that marks mRNA as “self” to prevent recognition by the IFN-induced RNA binding proteins RIG-I and IFIT1 (12-15).…”
Section: Introductionmentioning
confidence: 99%
“…These mRNA cap modifications have been shown to have a wide variety of functions. For example, the m 7 G modification in the mRNA cap recruits the translation initiation machinery for cap-dependent translation, and Cap 1 2’O methylation can further enhance this translation (8, 10, 11). mRNA cap 2’O methylation has also been shown to prevent degradation of modified transcripts by exoribonucleases or serve as a motif that marks mRNA as “self” to prevent recognition by the IFN-induced RNA binding proteins RIG-I and IFIT1 (12-15).…”
Section: Introductionmentioning
confidence: 99%
“…2'-O-methylation (Nm) is a common RNA modification. The addition of a methyl group to the 2' hydroxyl of the ribose moiety of a nucleoside creates Nm (reviewed in (4,5) ). Nm can occur at any nucleotide explaining the abundant nature of this modification.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have uncovered crucial roles for FTSJ1/TRM7 in normal and pathological conditions (reviewed in (4,5) ). While in S. cerevisiae , lack of TRM7 affected growth, FTSJ1 mutant mice showed impairment in their learning capacity as well as significantly reduced pain sensing (hypoalgesia) and altered gene expression profiles (40) .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they play a crucial role throughout all tRNA biogenesis steps, such as sequence maturation, folding, recycling and degradation. Interestingly, there is a crosstalk between the different modification pathways and a large amount of tRNA modification enzymes defects have been linked to human pathologies (Angelova et al, 2018;Sokołowski et al, 2018;Dimitrova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is found in tRNAs, rRNAs, snRNAs (small nuclear RNAs) at the 3' end of some small non-coding RNAs (such as piRNAs) and at some sites on mRNAs (Jordan Ontiveros et al, 2019). This modification plays a wide range of roles in RNA structure, stability and interactions (Dimitrova et al, 2019). It has been recently shown that Drosophila proteins CG7009 and CG5220 are the functional orthologues of yeast TRM7 (Pintard et al, 2002) and human FTSJ1 (Guy et al, 2015) respectively, which are involved in 2'-O-methylation of the anticodon loop of several conserved tRNAs substrates (tRNA-Leu, Trp, Phe) in different species, including Drosophila.…”
Section: Introductionmentioning
confidence: 99%